For vectors # mathbf a, mathbf b#, the length of the resultant vector, #mathbf c = mathbf a - mathbf b#, is:
#abs ( mathbf c ) = sqrt( (mathbf a - mathbf b) cdot (mathbf a - mathbf b))#
And:
#abs ( mathbf c )^2 = (mathbf a - mathbf b) cdot (mathbf a - mathbf b)#
#= mathbf a cdot mathbf a + mathbf b cdot mathbf b - 2 mathbf a cdot mathbf b #
And because:
#mathbf a cdot mathbf b = abs( mathbf a) abs( mathbf b) cos alpha#
#mathbf v cdot mathbf v = abs( mathbf v) abs( mathbf v) cos 0= |mathbf v|^2#
We have:
#abs ( mathbf c )^2 = sqrt (|mathbf a|^2 + |mathbf b|^2 - 2 |mathbf a| |mathbf b| cos alpha) #
#= 1^2 + 2^2 - 2 (1)(2) cos (pi/6) #
#= 5 - 2 sqrt 3#
#approx 1.56#